Moche murals at Pampa La Cruz, Huanchaco, North Coast of Peru - Prieto, Gabriel (2024)
Archaeological excavations at the Pampa La Cruz site have revealed Moche-style wall paintings in a ceremonial structure. This unique find constitutes the first case of this type of mural art in a non-monumental site of the Moche society reported in academic media. The analysis of this evidence suggests that it was a narrative inserted in an expansive political and religious program of Moche society around A.D. 600-700. Additionally, it suggests that this narrative art program was closely connected to an increase in ritual violence activities, particularly human sacrifice. The latter, however, seems to differ from cases of human sacrifice in monumental sites such as Plaza 3A in Huaca de la Luna. Finally, the presence of this mural and the Moche political/religious presence in Pampa La Cruz, suggests that this site, beyond having been a simple fishing village, may have played an important geopolitical role in the configuration of Moche power among the seventh and eighth centuries of our era.